TENGKULUK JAMBI DALAM PERSPEKTIF ETHNOMATEMATIKA: INTEGRASI BUDAYA LOKAL DALAM PEMBELAJARAN MATEMATIKA - Susanti, Ade; Hariyadi, Bambang; Zurweni, Zurweni; Haryanto, Haryanto (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2025)
Mathematics is often understood as an abstract discipline and independent of cultural values, whereas in the cultural practice of society, mathematical concepts are usually integrated into cultural traditions and artifacts. In the context of meaningful and culturally relevant mathematics education, it is essential to explore mathematical knowledge embedded in local cultural practices. Through a qualitative approach with ethnographic design, this study examines ethnomathematics on traditional headgear of Jambi Malay women, focusing on mathematical concepts integrated with the shape, motif, and technique of folding the navel. The study results show that at least 5 shapes of tenaculum represent geometric concepts such as folding symmetry patterns, geometric transformations, angles, and pattern repetitions that resemble flat shapes and 3-dimensional shapes. Each design and shape of the tengkuluk fold has geometric characteristics and philosophical values, such as harmony with nature and the social structure of the Jambi community. This research contributes to developing ethnomathematics-based mathematics learning design by integrating contextual, project-based learning, and inquiry approaches. Thus, this study not only enriches the ethnomathematical literature in Indonesia but also bridges the gap between modern science and local wisdom in the context of meaningful and culturally relevant mathematics education.